Triton X-114 fractionated subcellular proteome ofleptospira interrogansshows selective enrichment of pathogenic and outer membrane proteins in the detergent fraction - Thoduvayil, Sikha; Dhandapani, Gunasekaran; Brahma, Rahul; Devasahayam Arokia Balaya, Rex; Mangalaparthi, Kiran K.; Patel, Krishna; Kumar, Manish; Tennyson, Jebasingh; Satheeshkumar, P. K.; Kulkarni, Mahesh J.; Pinto, Sneha M.; Prasad, T. S. Keshava; et al. (Proteomics, 2020)
The Triton X-114-based solubilization and temperature-dependent phase separation of proteins is used for subcellular fractionation where, aqueous, detergent, and pellet fractions represents cytoplasmic, outer membrane (OM), and inner membrane proteins, respectively. Mass spectrometry-based proteomic analysis of Triton X-114 fractions of proteomic analysis ofLeptospira interrogansidentified 2957 unique proteins distributed across the fractions. The results are compared with bioinformatics predictions on their subcellular localization and pathogenic nature. Analysis of the distribution of proteins across the Triton X-114 fractions with the predicted characteristics is performed based on ``number'' of unique type of proteins, and ``quantity'' which represents the amount of unique protein. The highest number of predicted outer membrane proteins (OMPs) and pathogenic proteins are found in aqueous and pellet fractions, whereas detergent fraction representing the OM has the highest quantity of OMPs and pathogenic proteins though lower in number than the aqueous and pellet fractions. This leaves the possibility of an upsurge in pathogenic proteins and OMPs on the OM under pathogenic conditions suggesting their potential use to combat leptospirosis. Further, the Triton X-114 subcellular fractions are more correlated to enrichment of pathogenic proteins predicted by MP3 software than predicted localization.
Keywords: intensity-based absolute quantification; Leptospira; outer membrane protein; subcellular localization; Triton X-114